Recruitment and Selection Policies and Procedures and their effects on Organisational Performance: A Case Study - Nanor, Annibert; Owusu, Edward; Senyah, Mavis Mensah; Owusu, Evelyn Kumah Osei; Agyei, Samuel Kofi (Technium Social Sciences Journal, 2022)
This paper examines the impact that HR recruitment and selection policies and procedures have on organisational performance at the Ghana-India Kofi Annan Centre of Excellence in ICT (AITI-KACE). Drawing from a sample of 39 respondents, the study used the sequential explanatory mixed method design. Quantitative data and analysis were obtained using questionnaires. Qualitative data and analysis were obtained through interviews and focus group discussions. Results from the study revealed that AITI-KACE has a policy on recruitment and selection, which the organisation mostly adheres to. The sources of recruitment and selection were both internal and external. The results also revealed a significant link between recruitment and selection practices on organisational performance. The outcome of the study further showed that there was no significant link between recruitment and selection practices and the employment of competent staff. Political and socio-economic elements are primary influences on the selection of candidates. The study proposed that all prospective workers should be handled equally throughout the recruitment and selection processes. The study further recommended that formal guidelines and procedures on the recruitment and selection processes are appropriately adhered to, to guarantee that the best and most deserving workers are engaged.